2017
DOI: 10.1101/gad.296319.117
|View full text |Cite
|
Sign up to set email alerts
|

Structures of partition protein ParA with nonspecific DNA and ParB effector reveal molecular insights into principles governing Walker-box DNA segregation

Abstract: Walker-box partition systems are ubiquitous in nature and mediate the segregation of bacterial and archaeal DNA. Well-studied plasmid Walker-box partition modules require ParA, centromere-DNA, and a centromere-binding protein, ParB. In these systems, ParA-ATP binds nucleoid DNA and uses it as a substratum to deliver ParB-attached cargo DNA, and ParB drives ParA dynamics, allowing ParA progression along the nucleoid. How ParA-ATP binds nonspecific DNA and is regulated by ParB is unclear. Also under debate is wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 62 publications
2
64
0
Order By: Relevance
“…In C. crescentus ParB depletion or mutation quenches ParA dynamics, leading to ParA diffuse localisation (Ptacin et al ., ). It has been shown before that ParA‐DNA binding allows ParB movement (Schumacher and Funnell, ; Vecchiarelli et al ., ; Le Gall et al ., ; Zhang and Schumacher, ). Thus our results are consistent with general mechanism of ParA action in bacteria.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In C. crescentus ParB depletion or mutation quenches ParA dynamics, leading to ParA diffuse localisation (Ptacin et al ., ). It has been shown before that ParA‐DNA binding allows ParB movement (Schumacher and Funnell, ; Vecchiarelli et al ., ; Le Gall et al ., ; Zhang and Schumacher, ). Thus our results are consistent with general mechanism of ParA action in bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…However, more recent findings suggest, that ParA dimers (or short filaments) translocate partition complexes on the surface of the nucleoid through diffusion-ratchet mechanism. Additionally, it has been shown that chromosome elasticity may contribute to the movement of segrosomes (Vecchiarelli et al, 2010(Vecchiarelli et al, , 2014Hwang et al, 2013;Lim et al, 2014;Sanchez et al, 2015;Zhang and Schumacher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have described the main components of the mycobacterial chromosome segregation machinery, the ParA and ParB proteins, and have reported ParA interaction with a polar growth determinant DivIVA homologue (named Wag31 in mycobacteria) (Jakimowicz et al , ; Ginda et al , ; ; Uhía et al ., ), the exact mechanism of asymmetric chromosome segregation and the biological role of the ParA‐DivIVA interaction have not been investigated. In mycobacteria, as in most studied bacterial species ( Bacillus subtilis, Caulobacter crescentus, Vibrio cholerae, Myxococcus xanthus, Corynebacterium glutamicum , and Streptomyces coelicolor , but not Escherichia coli and some other γ‐proteobacteria), origin of chromosomal replication ( oriC ) regions are organised into complexes named segrosomes by ParB binding to oriC ‐proximal parS sites (Chaudhuri and Dean, ; Wang et al , ; Graham et al , ; Zhang and Schumacher, ). Usually immediately (but in some species after some cohesion time) following the initiation of replication, ParB complexes duplicate, and then one or both complexes are moved to their target cell locations.…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge of the determinants mediating the DNA-binding activity of P-loop ATPases is largely based on studies of canonical ParA homologs. For this group of proteins, two distinct modes of DNA binding, mediated by different regions of the dimer surface, have been reported (37,38). Moreover, the residues identified in previous studies are not universally conserved among DNA-binding members of the ParA-like ATPase family.…”
Section: Identification Of Dna-binding Residues On the Mipz Surfacementioning
confidence: 95%
“…Residues homologous to these arginines were later also implicated in the DNA-binding activity of PpfA from Rhodobacter sphaeroides and PomZ from Myxococcus xanthus (17,20). More evidence for the importance of positively charged amino acids has recently come from the crystal structures of ParA-DNA complexes formed by ParA homologs from Helicobacter pylori (HpParA) (37) and Sulfolobus solfataricus pNOB8 (38), which each identified several surface-exposed lysine residues that are in direct contact with the DNA ligand. However, the binding interface pNOB8 ParA was different from that of its H. pylori homolog or R. capsulatus PpfA (38), suggesting that ParA proteins could have evolved different modes of DNA binding.…”
Section: Introductionmentioning
confidence: 99%